The Effect of Work Motivation and Organizational Culture on Employee Performance at PT. Matahari Department Store Grage Mall Cirebon City - Dea Marina Fenawati; Dwi Septiyani; Muhammad Alwi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of work motivation and organizational culture on employee performance at PT. Matahari Department Store Grage Mall, Cirebon City. In an increasingly competitive business environment, employee performance is a fundamental factor in achieving organizational effectiveness. Work motivation plays a role in encouraging individuals to achieve work goals, while organizational culture creates a conducive environment for employee productivity. By using a quantitative approach with a survey method, where data is collected through questionnaires distributed to respondents who are employees of the company. Data analysis was carried out using multiple linear regression methods to test the relationship between independent variables and dependent variables. The results of the study indicate that work motivation has a positive and significant influence on employee performance. Likewise, organizational culture contributes significantly to improving individual performance within the company. Simultaneous tests also indicate that work motivation and organizational culture together have a significant influence on employee performance. These findings emphasize that companies need to pay attention to aspects of motivation and organizational culture in designing human resource management strategies to increase the company's productivity and competitiveness. Therefore, it is recommended that company management develop policies that support increased motivation and create a more adaptive and productive organizational culture.